Evaluation of a Diabetes Prevention Program Implementation in a Student-Run Free Clinic Setting - Huszagh, Meredith; Hatcher, Jeremy; Grimaldi, Carolina Gomez; Kloosterman, Nicole; Carranza-Leon, Daniel; Li, Xuanyi; Sulieman, Lina; Chakkalakal, Rosette; Niswender, Kevin (Journal of Student-Run Clinics, 2022)
Introduction: The Diabetes Prevention Program (DPP) can prevent or delay the development of type 2 diabetes in at-risk individuals. Although low-resource and minority communities have higher rates of type 2 diabetes, these communities often have limited DPP participation due to cost and program accessibility. We evaluated whether a high-fidelity, reduced-cost 16-week DPP could feasibly be implemented by student volunteers and be effective in facilitating the target 5% weight loss goal among participants. Methods: Uninsured, Spanish-speaking participants and their invited guests were recruited from Vanderbilt University Medical Center’s student-run clinic. Weekly DPP sessions were conducted using the CDC’s Prevent T2 curriculum in Spanish, delivered in-person for 6 weeks and virtually for the remaining 10 weeks due to the Coronavirus Disease 2019 pandemic. Participant attendance and weight data were collected. Pre- and post-program health-related quality of life was assessed using the EuroQoL 5D5L tool, and qualitative program feedback surveys were administered. Changes in weight and quality of life as a function of program session attendance and patient demographics were determined primarily using Wilcoxon tests. Results: Of the 17 participants actively engaged in the student-led DPP, 13 were clinic patients and 4 were invited guests. The median weight loss achieved by participants was 5.90% of their total body weight. 13 of the 17 participants (76.50%) achieved the 5% weight loss goal. Age, sex, pre-program body mass index, and English proficiency were not associated with the achievement of the 5% weight loss goal. Though not statistically significant, patients’ average self-scored general health rating (0-100) improved from 72.30 to 81.50 (p=0.12), and the greatest reductions in health limitations were reported with regards to pain (1.94 to 1.70, p=0.28) and daily activities (1.53 to 1.35, p=0.36). Conclusion: A student-run DPP implementation among low-resource participants is feasible and appears capable of achieving the target 5% weight loss.